Sistemul public de servicii medicale din România în context european - Stanciu, Mariana (Calitatea Vieții, 2013)
This article opens a debate of great interest for the Romanian present society: the current situation of the national health services reform and its social effects until now. This is not an exhaustive aproach of the field, but rather an overview of some challenges and difficulties that Romania has encountered in the tendency to modernize its public health care system. The reform of the public system of health services from Romania, started in 1998, but yet unfinished, only multiplied the social costs of the medical care, on the background of the continuously decreasing of the quality of the services offered and of the population access to the services. After 15 years of reform, Romania is still on the last place in the European top of the public health service quality. The Euro Health Consumer Index – EHCI is a synthetic standard assessor of the performances belonging to European public health systems. Putting in a single formula more analitycal indicators regarding the quality of public health services EHCI provides a comprehensive description of the quality of a public health system. In spite of it, at least in Romania, there still are many politicians who think that reforming public health services is only a matter of financing the system. This article indicates the tendency of state to stop the financing for some polyclinics and hospitals, clearly showing the social mission of the public health services, in the conditions of the entering on the free market of some private health services. The description of the defficient material endowments of the public health system and of rather disballanced cover of the system with medical staff, raises the problem of adopting new social and medical policy, in order to improve the quality of health services. In the context are included also some solutions applied by other European systems with superior performances, for alleviating some specific difficulties. The process of reforming the public health system în Romania is not an easy task for anybody, it supposes a mature strategic vision based on a deep knowledge of the existing system and demands consistent financial resources. But first of all, it supposes a steady political will, a long term co-ordination of the process by experts and last, but not least, the medical institutions and staff colaboration. This paper uses as main sources of databases Eurostat, National Institute for Statistics, but contains also some opinions of the medical staff and patients.